Analisis Pengaruh Massa Beban Terhadap Pertambahan Panjang dan Konstanta Pegas - Diah Rahmawati; Adam Malik (Jurnal Pendidikan Fisika dan Sains (JPFS), 2023)
This study aims to analyze the effect of the mass of the load on the increase in length and the value of the spring constant. Spring elasticity is the property or ability of a spring to experience deformation when given a force or load, but then can return to its original shape and size when the force or load is removed. Hooke's law is the basic principle that describes the elasticity of springs. This law states that the force exerted on a spring is proportional to the change in length or change in angle. This study uses Amrita VLab as a tool to observe and study spring elasticity through virtual experiments.